ANALISIS EOSINOFIL DARAH TERKAIT RADANG SEL GINJAL AKUT/ NEFRITIS INTERSTISIAL AKUT (NIA) - Yedid Lebang; Sulina Yanti Wibawa; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Acute Interstitial Nephritis (AIN) is the main cause of acute renal failure because of hypersensitivity to many antibiotics and otherdrugs that potent to induce allergic response in renal interstitial tissue. Gold standard for AIN diagnosis upheld from clinical sign,laboratory, USG, Gallium renal tests and renal biopsy. A cross sectional study was carried out among 120 (AIN) patients and none (AIN)from the Paediatrics and Internal Medicine Department Wahidin Sudirohusodo hospital from June until September 2008. Eosinophilcount was performed using haematology auto analyser. The data was analyzed by Mann-Whitney test using SPPS for windows. Thetotal 120 samples consisted of 60 samples of AIN and 60 samples Non AIN were included in this study. Mean eosinophil in AIN 4. 9 %and non AIN 3. 1%. There were statistical difference of eosinophil level between AIN and non AIN with p < 0. 00. Eosinophil level canbe used to differentiated between AIN and non AIN in conjunction to the clinical sign.